Statistics for accountants : text in statistical science - Letchford, Stanley (Texts in statistical science series., 1994)
this book provides a simple introduction to statistics with special emphasis on the applications of the subject tto accountancy. its approach is based on the assumption thatm although accountants are not expected to be highly qualified statisticians .